Old english poetic paraphrases of the song of the three youths from the poems Daniel and Azarias - Maria Yatsenko (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The paper contains the translations of the two Old English poetic paraphrases of the Song of the Three Youths, preserved in the poems Daniel and Azarias. The translation follows the principle of equilinearity. The author aims at organizing the poetic line according to the principle of alliterative poetry: using the consonance of 2–4 root morphemes in the poetic line. The Old English paraphrase of the Song of the Three Youths is the key part of the central episode in the poem Daniel, presenting the rescue of the Three in the fiery furnace.